Contaminant bacteria in traditional-packed honey - Pramesti, Hening Tjaturina; Hardjawinata, Karlina; Fath, Putra Qadri (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2007)
Honey may be contaminated by microorganisms during its harvesting, processing, and packaging. Honey selected for clinical purposes must safe, sterile, and contain antimicrobial activity, so it must be evaluated using laboratory testing. The aim of this descriptive laboratory study was to isolate and identify the bacterial contaminant in the traditional-packed honey dealing with the use of honey for medical purposes. the colony forming units of honey sample cultured on blood agar were counted using Stuart bacterial colony counter. The suspected bacterial colonies were isolated and identified based on cultural morphology characteristics. The isolates of suspected bacterial colonies were stained according to Gram and Klein method and then were examined by the biochemical reaction. The results showed that there were two contaminant bacteria. Gram-positive cocci which were presumptively identified as coagulase-negative Staphylococci and gram-positive rods which were presumptively identified as Bacillus subtilis. In conclusion, the contaminant bacteria were regarded as low pathogen bacteria. The subtilin enzyme of B subtilis may cause an allergic reaction and coagulase-negative Staphylococci, Staphylococcus epidermidis is also an opportunist pathogen. Inevitably, for medical purposes, traditional-packed honey must be well filtered, water content above 18%, and standardized sterilization without loss of an antibacterial activity or change in properties.